The effect of the home on the school in Trinidad - Dyer, Patrick B. (Oxford University Press, 1976)
Two hypotheses are examined: 1) the relationship between the measure of school achievement (Iowa Test of Basic Skills) and the Index of Educational Environment in the Home (IEE) will be greater than that between school achievement and Index of Social Background (ISB), and 2) there will be statistically significant differences in the independent contribution of measured intelligence (non-verbal and verbal), ISB and IEE to the prediction of school achievement. Specific environmental variables in the home were observed such as achievement press, language models, academic guidance, activeness in the family, intellectual interests, and the home, and work habits emphasized in the home. Both hypotheses were upheld. The findings, which have implications for both theory and practice, suggest that parents' efforts to enrich the educational environment in the home should work to the advantage of the child; that the teacher and administrator, making use of a knowledge of the home environment, should be in a better position to help the child in his academic progress. Educators in the Caribbean are advised to work on improving the assistance that can be given to the child by the home. This work is envisaged as helping the parent to improve the educational environment of the home. The home will thus be truly complementing the work done by the school, to the benefit of the child
Keywords: Sociology of education